Sistem Pendukung Keputusan Seleksi Pemain Futsal dengan Menggunakan Metode Naive Bayes - Anam, Moh. Syaiful; Utomo, Yudo Bismo; Kurniadi, Harso (Insect (Informatics and Security): Jurnal Teknik Informatika, 2025)
Futsal is a sport that has a high level of competition, both at national and international levels. The success of a futsal team depends on the quality of the players selected, so player selection is an important aspect in building a competitive team. Player selection is usually based on the coach's experience, which can be subjective and less systematically measurable. Therefore, a more objective and accurate method is needed in the futsal player selection process. This study develops a Decision Support System (DSS) that aims to select futsal players using the naïve bayes method. This method is used because of its ability to perform probabilistic-based classification, which can help in assessing player eligibility based on several criteria. The parameters analyzed include technical skills, speed, endurance, passing accuracy, and other physical aspects. The results obtained from the calculation using the system with the naïve bayes method reached 90% with details of 9 appropriate results and 1 inappropriate result.